Lasten ja nuorten yksinäisyys ja ostrakismi kuntapalveluiden yhdyspinnoilla – osallisuudesta apua kompleksiseen haasteeseen - Kyösti, Anni; Laasanen, Miia (Hallinnon tutkimus, 2025)
Loneliness and ostracism, have serious consequences for the well-being of children and young people. This qualitative research examines how the municipal service system (education and youth services), recognizes children and young people´s loneliness and ostracism. Another question is how children's and young people's views on loneliness and ostracism are considered in the development of the service system. The topic is examined with the help of complexity theory and children´s participation.
Identifying the experiences of loneliness and ostracism is challenging. The phenomenon is located at the interface of different actors and levels of service systems which makes it complex. Children and young people, professionals as well as families are needed to recognize the phenomenon. Also, communication and cooperation between them is essential.
Key words: Loneliness, ostracism, education service